Harga diri dan resiliensi pada perempuan dewasa awal yang bekerja sebagai tulang punggung keluarga - Sherly Faulina Sianturi; Arthur Huwae (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
Working as the breadwinner of the family is generally done by men. However, in the current era, women are also the backbone of the family, especially women in early adulthood. Various problems faced by early adult women who work as the backbone of the family have an impact on individual resilience. To achieve good resilience, good self-esteem is needed so that individuals can overcome the problems they face. This study aims to determine the relationship between self-esteem and resilience in early adult women who work as the backbone of the family. Quantitative correlational design is the method employed. The sample in this study amounted to 119 participants aged 20-40 years using incidental sampling. The research measurement used the Self-Esteem Inventory (a = .938) and the Adult Resilience Scale (a = .922). The research data analysis method used the Spearman Rho correlation test. The results showed that there was a significant positive relationship between self-esteem and resilience in young adult women who worked as the backbone of the family (r = .495 and sig. = .000). Self-esteem makes an effective contribution of 24.5% to resilience. This indicates that self-esteem is one of the factors associated with increased resilience. It is expected that early adult women who work as the backbone of the family will maintain good self-esteem every day to achieve good resilience in overcoming any problems in their lives.